Analysis of whole genome‐wide methylation and gene expression profiles in visceral omental adipose tissue of pregnancies with gestational diabetes mellitus. Issue 7 (July 2018) - Deng, Xingli; Yang, Yulin; Sun, Hao; Qi, Wenjin; Duan, Yong; Qian, Yuan
Abstract : Background: : DNA methylation is the most extensively studied epigenetic modification which had been suspected to be involved in the progress of gestational diabetes mellitus (GDM). It is vital to investigate the expression profile and methylation profile in the GDM adipose tissue samples to learn more about the relationship between the two profiles. Methods: : Illumina Human Methylation 450 k DNA Analysis Beadchip and whole Human Gene Expression Array were selected to screen for methylation and gene expression in the omental visceral adipose tissue of pregnant women. Validation of methylation of DMGs was conducted by bisulfate pyrosequencing and expression of DEGs by q RT‐PCR. Results: : Global gene methylation profiling and whole genome expression profiling were conducted in visceral omental adipose tissue (VOAT) between GDM and normal pregnancies. Compared with controls, 935 genes were commonly dysregulated in the GDM group, including 450 down‐regulated DEGs and 485 up‐regulated DEGs. The Seven overlapping genes between DEGs and DMGs were extracted, including C10orf10, FSTL1, GSTT1, HLA‐DPB1, HLA‐DRB5, HSPA6 and MSLN . Among them, C10orf10, FSTL1, GSTT1, HLA‐DPB1, HLA‐DRB5 showed hypermethylation and up‐regulated expression, while HSPA6 show hypomethylation and down‐regulated expression. Typical negative correlation between gene expression and DNA methylation level was only found in MSLN with significant hypermethylation in the CpG island and downregulated transcription. No gene was found to be significantly hypomethylated in the CpG islands and unregulated transcription. Conclusion: : We found that antigen processing and presentation pathway and immune‐related genes were closely associated with gestational diabetes mellitus in the visceral omental adipose tissue of Chinese pregnant women, based on the integration analysis of expression and methylation profiles. These results may be valuable for the prognostic biomarkers and future therapeutic targets.